The Effectiveness of Lexicon Card Media Assisted by Minimum Competency Assessment on Students’ Learning Comprehension - Mia Rahmaniar Zumarnis; Panca Dewi Purwati; Trimurtini (Universitas Pendidikan Ganesha, 2024)
The low student learning outcomes in Indonesian language learning content in class IV are caused by teachers tending to use lecture methods, which causes students to become bored. This research aims to analyze the effectiveness of lexicon card media assisted by minimal competency assessment on students' understanding compared to conventional methods. The method used in this research uses a Quasi Experiment type with a Non-equivalent Control Group research design. The methods used to collect data are interviews, observation, documentation and tests. The instruments used to collect data were questionnaires and test questions. The population of this study was 111 students. The sampling technique used is Nonprobability Sampling. The data analysis technique used is quantitative descriptive analysis and inferential statistics. The results of research on the use of lexicon card media assisted by minimum competency assessments can improve student learning outcomes. The results of the student understanding test increased from the pretest to the post-test, and the average of the experimental class was higher than the control class. It was concluded that the effectiveness of lexicon card media assisted by minimum competency assessments in understanding the ideas of narrative texts had an influence in improving student learning outcomes compared to conventional methods.